Pelatihan Inovasi Kain Tapis Krui di Pekon Way Sindi Kabupaten Pesisir Barat - Achmad, Feerzet; Satria, Arysca Wisnu; Saputri, Desi Riana; Auriyani, Wika Atro; Supriyadi, Didik (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2021)
Tapis is a traditional Indonesian woven which is produced by using a non-machine weaving loom. Tapis is an ornamental motif-based manifestation, especially for the people of Pesisir Barat's local history and beliefs. The issues that occur with Tapis weaving craftsmen are production infrastructure, minimal market availability, a lack of knowledge, and their skills for product innovation. The people of Pesisir Barat require empowerment and support to develop the knowledge and abilities of Tapis weaving craftsmen in the production of tapis derivative products. These items will support the Pesisir Barat's tourism industry succeed. This community service activity was carried out by holding coaching for the Kerudung Sakti and Kiluk Andan Tapis Crafts Group in Way Sindi Village, Karya Penggawa, Pesisir Barat district. This training is expected to improve the community's knowledge and skills in developing various souvenir products and craft accessories made from Tapis derivative products.